Body techniques of health: Making products and shaping selves in northwest Alaska - Lincoln, Amber (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2010)
This paper considers the connections between body technologies and wellness. Residents of northwest Alaska suffer disproportionately from social and behavioural illnesses. In Nome and Kotzebue, Inupiat and Yupiit women prescribe traditional activities, such as processing food and making tools and crafts from local harvests, to family members in an effort to promote their well-being. At the same time, Alaska Native institutions organise subsistence activities as a means to generate healthy living among tribal members. This paper seeks to understand why so many Nome and Kotzebue residents view traditional activities as a solution to locally perceived social ills such as substance abuse. The ethnography is based on two groups of women’s collective efforts: processing of seal into black meat and learning to make grass baskets—activities locally identified as “traditional” practices. Firstly, this article highlights the body practices developed within spaces of women’s collective production. Secondly, it describes the contemplation and narratives that emerge within these spaces. Lastly, it explores the relationship between body practice and verbal expression, and how this relationship promotes wellness. Analysing Inupiat and Yupiit traditional activities within the framework of technological process reveals how making traditional products also shapes healthy individuals.